Out of Proportion? On Surveillance and the Proportionality Requirement. - Rønn, Kira Vrist; Lippert-Rasmussen, Kasper (Ethical Theory & Moral Practice, 2020)
In this article, we critically scrutinize the principle of proportionality when used in the context of security and government surveillance. We argue that McMahan's distinction from just warfare between narrow proportionality (cases in which a threatener is liable to suffer the harms inflicted upon him in the course of surveillance) and wide proportionality (involving harms inflicted on non-liable individuals) can generally apply to the context of surveillance. We argue that narrow proportionality applies more or less directly to cases in which the surveilled is liable and that the wide proportionality principle applies to cases characterized by 'collateral intrusion'. We argue, however, that a more demanding criterion than the lesser-evil justification that wide proportionality frequently entails is necessary in cases characterized by intentional intrusion upon non-liable individuals (e.g. some cases of mass surveillance). The distinction between foreseeing and intending intrusion into the lives of individuals who are not liable has not previously been specifically addressed in discussions concerning surveillance ethics. This specification is thus increasingly important due to the general growing tendency for adherence to the precautionary principle and policies aimed at anticipating criminal acts before they are committed. Preventive surveillance of non-liable actors is considered an important instrument for obtaining this aim and thus calls for moral scrutiny in terms of permissibility and proportionality. We suggest the concept 'wide proportionality +' which applies to cases of intentional intrusion of non-liable individuals.